Efficient activation of persulfate by Fe3O4@β-cyclodextrin nanocomposite for removal of bisphenol A. Issue 27 (19th April 2018) - Zhu, Yanyan; Yue, Min; Natarajan, Vinothkumar; Kong, Lingshuai; Ma, Long; Zhang, Yuqiang; Zhao, Quanqin; Zhan, Jinhua
Abstract : Persulfate (PS), the most commonly used activator for in situ chemical oxidation (ISCO), could couple with Fe3 O4 @β-CD for effectively degrading BPA. Abstract : Experimental studies were conducted to investigate the degradation of bisphenol A (BPA) by using persulfate (PS) as the oxidant and Fe3 O4 @β-cyclodextrin (β-CD) nanocomposite as a heterogeneous activator. The catalytic activity was evaluated in consideration of the effect of various parameters, such as pH value, PS concentration and Fe3 O4 @β-CD load. The results showed that 100% removal of BPA was gained at pH 3.0 with 5 mM PS, 1.0 g L −1 Fe3 O4 @β-CD, and 0.1 mM BPA in 120 min. Further, the catalytic activity of Fe3 O4 @β-CD nanocomposite was observed as much higher when compared with Fe3 O4 nanoparticles alone. The sulfate and hydroxyl radicals referred to in the Fe3 O4 @β-CD/PS system were determined as the reactive species responsible for the degradation of BPA by radical quenching and electron spin resonance (ESR) tests. In addition, the catalyst also possessed with accepted reusability and stability. On the basis of the results of the effect of chloride ions (Cl − ), β-CD was found to play a crucial role in reducing interference from Cl − ions, and lead to achieve higher removal efficiency for BPA in Fe3 O4 @β-CD/PS system. A possible mechanistic process of BPA degradation was proposed according to the identified intermediates by gas chromatography-mass spectroscopy (GC-MS).